ANALISIS KINERJA JARINGAN SWITCHING CLOS TANPA BUFFER - Rizki Syahputra; Hafni Hafni (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2018)
The Clos Network is a switching network that represents an ideal theory of many level telephone switching systems in practice. analyze the performance of the Clos switching system on processor-memory interconnects. The performance analyzed is the probability of blocking. To measure the performance of the Clos switching system, you must first know how to build a network, how it works, and what performance can be measured from the Clos switching network without buffers. Blocking probability will be calculated using the Lee method and Jacobeus method. The results obtained show an accurate calculation of the Clos switching system that is the probability of blocking with the Lee and Jacobeus method with the parameters of the number of input switches n (with values of 64, 120, and 240), the number of switches between m (with a value of 64, 68, 72, 76, 128, and 256) and the probability given by the input and output links is busy Ï (with a value of 0.6 to 0.95 with a range of 0.05), where with the increase of the switch value the probability blocking value with the Lee method and the Jacobeus method of the switching system it decreases with the difference in the results obtained is quite small. For the value of n = 64, m = 64, Ï = 0.6, the value of the blocking probability is smaller that is 7.97365x10-6 for the Pb value of the Lee method and 7.15779x10-6 for the Pb value of the Jacobeus method and for n = 240, m = 256, and Ï = 0.6, the smaller Pb value is 1.3263x10-25 for the Pb value of the Jacobeus method and 1.24705x10-24 for the Lee Pb method value. If the difference in the number of input switches and switches between is not too large, both methods (Lee and Jacobeus) can be chosen because they show almost the same performance, but if the difference in the number of input switches and between the greater, the Jacobeus method produces better performance